THE VIEW OF CONSTITUTIONAL LAW ON THE RETROACTIVE EFFECT OF MATERIAL CONTENTS OF LAWS AND REGULATION IN INDONESIA - Randy Agus Setiawan; Yhannu Setyawan; Malicia Evendia (PRANATA HUKUM, 2023)
Retroactive regulation of the contents of laws and regulations in Indonesia based on the provisions of the non-retroactive principle and the principle of legality is not allowed as an embodiment of the protection of human rights which are non-derogable rights. This arrangement is confirmed in Article 28I paragraph (1) of the 1945 Constitution and Article 1 paragraph (1) of the Criminal Code (KUHP). However, the fact is that there are still laws and regulations that are retroactively enforced and are still in effect today. The purpose of this research is to analyze retroactive provisions whether they may apply according to Constitutional Law. This research is a normative legal research by conducting a review of retroactively enforced laws and regulations using a statutory, case and conceptual approach. The results of the study concluded that retroactive validity is constitutionally not in line with the 1945 Constitution but may be enforced on the basis of its validity, namely the provisions of Article 28J paragraph (2) and Law Number 1 of 2023 concerning the Criminal Code which transforms absolute provisions (non derogable rights) is relative.